Repair of ischemic ventricular septal defect with and without coronary artery bypass grafting. Issue 5 (1st April 2020) - Horan, Dylan P.; O'Malley, Thomas J.; Weber, Matthew P.; Maynes, Elizabeth J.; Choi, Jae Hwan; Patel, Sinal; Challapalli, Jothika; Luc, Jessica G.Y.; Entwistle, John W.; Todd Massey, H.; Morris, Rohinton J.; Tchantchaleishvili, Vakhtang
Abstract: Background and Aim of the Study: Ventricular septal defect (VSD) following myocardial infarction (MI) is a relatively infrequent complication with high mortality. We sought to investigate the effect of concomitant coronary artery bypass graft (CABG) on outcomes following post‐MI VSD repair. Methods: Electronic search was performed to identify all relevant studies published from 2000 to 2018. Sixty‐seven studies were selected for the analysis comprising 2174 patients with post‐MI VSD. Demographic information, perioperative variables, and outcomes including survival data were extracted and pooled for systematic review and meta‐analysis. Results: Single‐vessel disease was most common (47%, 95% confidence interval [CI], 42‐52), left anterior descending coronary artery was the most commonly involved vessel (55%, 95% CI, 46‐63), and anterior wall was the most commonly affected territory (57%, 95% CI, 51‐63). Concomitant CABG was performed in 52% (95% CI, 46‐57) of patients. Of these, infarcted territory was re‐vascularized in 54% (95% CI, 23‐82). A residual/recurrent shunt was present in 29% (95% CI, 24‐34) of patients. Of these, surgical repair was performed in 35% (95% CI, 28‐41) and transcatheter repair in 11% (95% CI, 6‐21). Thirty‐day mortality was 30% (95% CI, 26‐35) in patients who had preoperative coronary angiogram, and 58% (95% CI, 43‐71) in those who did not ( P < .01). No significant survival difference observed between those who had concomitant CABG vs those without CABG. Conclusions: Concomitant CABG did not have a significant effect on survival following VSD repair. Revascularization should be weighed against the risks associated with prolonged cardiopulmonary bypass.